PENGARUH PENERAPAN MODEL PEMBELAJARAN AKTIF TIPE TRADING PLACES TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN TARUSAN - Sartika, Sri Dewi; Edriati, Sofia; Cesaria, Anna (STKIP PGRI Sumbar, 2013)
This motivation of this research is about studentsâ understanding of mathematical concepts that are low. Â The students are lazy to give questions and opinions that the material is least understood. This is looked from the result of studentsâ mathematics learning at class VIII MTsN Tarusan. The purpose of this research is to know studentsâ understanding of mathematical concept that applay active learning model type trading places which is more good than studentsâ understanding of mathematical concept that applay convensional learning at class VIII MTsN Tarusan. The type of this research is experiment research with random sampling. The data analysis uses uji t, Â Â and = 1,645. Because of Â . Thus, the hypothesis in this research is accepted. In briefly, studentâ understanding of mathematical concept use active learning model type trading placesÂ which is more good than studentsâ understand of mathematical concept by using conventional learning at class VIII MTsN Tarusan.